Hubungan Dukungan Keluarga dengan Kecemasan Pasien Preoperasi di Rumah Sakit Umum Daerah Meuraxa Kota Banda Aceh - Elvi Savira; Urip Pratama; Riyan Mulfianda (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
The surgery often causes anxiety, which has an impact on physical and psychological conditions of preoperative patients. The data from WHO shows that 50% patients all over the world experienced anxiety, where 5-25% patients are between 5 and 20 years old, and 50% patients are 55 years old. Pre-operational anxiety reaches 534 million patients. Many factors affect anxiety in patients, including family support. This study aims to acknowledge the correlation between family support and anxiety of post-surgery patients in Meuraxa Regional General Hospital, Banda Aceh. This study employs an analytical correlational method with a cross-sectional approach by involving 51 patients selected using an accidental sampling technique. A family support questionnaire is adopted from Nurwulan, with a Cronbach's alpha 0.856. The questionnaire of anxiety using the APAIS scale of Cronbach's alpha 0.825. Univariate and bivariate analysis using the chi-square test. The results indicate that among 51 respondents, the level of anxiety is in a medium state, as 26 respondents (51.0%), family support is in the high category, 47 respondents (92.2%), with a P-value 0.026 (P-value < 0.05). In conclusion, there is a significant relationship between family support and preoperative anxiety at Meuraxa General Hospital Banda Aceh. Families are expected to continuously provide emotional, informational, instrumental, and appraisal support so that patients feel calmer, are able to reduce excessive anxiety, and are better prepared to undergo surgery.